Teaching Software Testing in an Algorithms and Data Structures Course - Arcuri, Andrea (2020 IEEE International Conference on Software Testing, Verification and Validation Workshops (ICSTW), 2020)
In this paper, we report and share our experience on introducing the teaching of Software Testing in an Algorithms and Data Structures course. The goal was twofold: (1) help in the teaching of the complex subject of algorithms and data structures and (2) start to make the student familiar with the topic of software testing. We report on the lessons learned in such endeavor and on the results of a student survey, after the course was completed. How the teaching of software testing was introduced was positively evaluated by the students. All our teaching material is freely available online on GitHub.